1990
DOI: 10.1113/jphysiol.1990.sp018116
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of neomycin on slowly adapting type I and type II cutaneous mechanoreceptors in the anaesthetized cat and rat.

Abstract: SUMMARY1. Slowly adapting type I (SAI) and type IL (SAII) mechanoreceptors in the skin were studied in anaesthetized cats and rats employing mechanical stimuli every 30 s. Individual stimuli rose within 200 ms to a plateau force which was kept constant through a feedback control unit for 2000 ms.2. In cats, close arterial infusion of neomycin (2-5 mg/min) as sulphate was given through a side branch into the femoral blood stream for 5, 10 or 20 min at a rate of 0-025 ml/min. At other times saline was infused at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…This notion is compatible with a vast amount of previous circumstantial evidence, e.g. irregular discharge patterns of cat SA type I units suggesting release of transmitters from Merkel cells (Horch, Whitehorn & Burgess, 1974); selective decreases of mechanical responses of SA type I units by perfusion of Ca2" channel blockers (Yamashita et al 1986); correlation of decreased responses of SA type I units with reduction in Merkel cell granules in a hypoxic environment (Findlater, Cooksey, Anand, Paintal & Iggo, 1987); susceptibility of SA type I units to neomycin suggesting the presence of functional synapses from Merkel cells to nerve terminals (Baumann, Hamann & Leung, 1990). The possibility has been raised that the nerve terminal is mechanoreceptive under certain conditions, such as mechanical stimulation with high frequency components (Gottschaldt & VahleHinz, 1981).…”
Section: Discussion Discrepancy Between Present and Previous Studiesmentioning
confidence: 99%
“…This notion is compatible with a vast amount of previous circumstantial evidence, e.g. irregular discharge patterns of cat SA type I units suggesting release of transmitters from Merkel cells (Horch, Whitehorn & Burgess, 1974); selective decreases of mechanical responses of SA type I units by perfusion of Ca2" channel blockers (Yamashita et al 1986); correlation of decreased responses of SA type I units with reduction in Merkel cell granules in a hypoxic environment (Findlater, Cooksey, Anand, Paintal & Iggo, 1987); susceptibility of SA type I units to neomycin suggesting the presence of functional synapses from Merkel cells to nerve terminals (Baumann, Hamann & Leung, 1990). The possibility has been raised that the nerve terminal is mechanoreceptive under certain conditions, such as mechanical stimulation with high frequency components (Gottschaldt & VahleHinz, 1981).…”
Section: Discussion Discrepancy Between Present and Previous Studiesmentioning
confidence: 99%
“…Electrophysiological in vivo studies have suggested the involvement of chemical synaptic transmission in the transduction process of the mammalian SAI mechanoreceptor (Findlater, Cooksey, Anand, Paintal & Iggo, 1987;Pacitti & Findlater, 1988;Baumann, Hamann & Leung, 1990) and of counterparts in frogs (frog type I mechanoreceptor) (Yamashita, Ogawa & Taniguchi, 1986). The highthreshold (L-type) Ca2" channel in Merkel cells may contribute to release of the transmitter as is the case for the same channel in sensory receptor cells such as hair cells (Ohmori, 1984;Hudspeth & Lewis.…”
Section: Y Yamashita and Otihersmentioning
confidence: 99%
“…Within the thickened epidermis of touch domes, the peripheral terminals of SAIs form expanded disc-like endings that lie in synapse-like apposition to Merkel cells in the basal epidermis (Munger, 1965;Iggo and Muir, 1969). The latter are neural crest-derived neuroendocrine cells (Szeder et al, 2003a) that appear to play an essential role in the transduction of mechanical stimuli into electrical activity of SAI afferents (Findlater et al, 1987;Iggo et al, 1988;Baumann et al, 1990;Ikeda et al, 1994;cf. Nurse and Cooper, 1988;Mills and Diamond, 1995).…”
mentioning
confidence: 99%